The Application of Neuro Linguistic Programming (NLP) on Cognitive Function and Stress Reduction - Hendriana, Deni; Komarudin, Komarudin; Mulyana, Raden Boyke (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
An approach or analysis of a problem that is expressed in the description of cognitive function and the reduction in stress levels experienced by athletes as a result of a pandemic situation so that there is no decrease in athlete's performance, several alternatives are needed that can maintain the athlete's condition. Based on the problems mentioned, the aim of this research is to evaluate the application of Neuro-Linguistic Programming (NLP) on cognitive function and stress reduction of basketball athletes. The method used in this research is the experimental method. The population in this study was 25 athletes in the sport of basketball at the Crows club. The number of samples is the total population of 25 athletes and the technique used is purposive sampling. The instrument for cognitive function uses the Montreal Cognitive Assessment (MoCA) and the instrument used for the level of stress is the DASS-21 Questionnaire (Depression Anxiety Stress Scale) developed by Lovibond. S. H and Lovibond. P. H (1995). The results of the study regarding the effect of the application of Neuro-Linguistic Programming (NLP) on cognitive function and stress levels can be concluded that there is a significant effect indicated by a significance value (sig.) Of 0.000, less than 0.05 (0.000 <0.05). The different test between the application of Neuro-Linguistic Programming (NLP) on cognitive function and stress reduction found that there was a difference in the effect between the application of Neuro-Linguistic Programming (NLP) on cognitive function and stress reduction marked with a 2-way (t-tailed) significance value of 0.000 < 0.05. Overall, the conclusion of this study is that the application of psychological training, especially the use of the Neuro-Linguistic Programming (NLP) method have positive effect on cognitive function and stress levels of basketball athletes during the COVID-19 pandemic.